2011
DOI: 10.1152/ajprenal.00071.2011
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous BMP-7 is a critical molecular determinant of the reversibility of obstruction-induced renal injuries

Abstract: Manson SR, Niederhoff RA, Hruska KA, Austin PF. Endogenous BMP-7 is a critical molecular determinant of the reversibility of obstruction-induced renal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…We and others have shown that Grem1 levels increase during DN whereas levels of BMP-7 decrease [33,46]. Strategies that stimulate BMP-7 signalling have been shown to attenuate renal fibrosis [5,[12][13][14][15][16][17], and reductions in Grem1 levels have a similar beneficial effect in mouse models of DN [32,37]. In vivo reduction of Grem1 via siRNA targeting recovered BMP-7 levels, suggesting that elevated Grem1 may have a role in repressing BMP-7 in DN [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that Grem1 levels increase during DN whereas levels of BMP-7 decrease [33,46]. Strategies that stimulate BMP-7 signalling have been shown to attenuate renal fibrosis [5,[12][13][14][15][16][17], and reductions in Grem1 levels have a similar beneficial effect in mouse models of DN [32,37]. In vivo reduction of Grem1 via siRNA targeting recovered BMP-7 levels, suggesting that elevated Grem1 may have a role in repressing BMP-7 in DN [37].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas BMP-4 has been shown to contribute to renal fibrosis, conflicting evidence exists for the pro-or anti-fibrotic role of BMP-2 in this process [8][9][10][11]. BMP-7 is thought of as anti-fibrotic, and has been the focus of many groups who demonstrated its anti-fibrotic activity in models of diabetic nephropathy and other kidney fibrotic diseases [5,[12][13][14][15][16][17]. To date, however, efforts to translate these data into BMP-7-centred treatment of fibrosis have been rather slow to develop [18,19] Canonical BMPs signalling involves the Smad pathway, where BMP dimers bind to type I and type II BMP receptors leading to the formation of a hexameric complex, triggering receptor phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Irreversible UUO allows the study of inflammation and tissue injury including the role of various leukocytes and mediators [1][2][3]10 whilst study of the R-UUO model enables researchers to explore the resolution of renal injury and associated tissue remodeling. 6,7,[11][12][13][14][15] Other investigators have used different methods to induce and reverse ureteric obstruction. In the first description of the R-UUO model, the left ureter of male C57BL/6 mice was obstructed with an atraumatic microvascular clamp via a flank incision.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has found that treatment with BMP-7 promotes the formation of Smad1/5/8-Smad4 protein complexes, but decreases the formation of Smad2/3-Smad4 protein complexes as well as the expression of TGF-β-dependent, profibrotic genes. Since BMP-7 does not affect TGF-β levels or Smad2/3 activation, this suggests a mechanism where TGF-β and BMP signals are mutually antagonistic by competing for a limited pool of Smad4 to induce transcriptional responses (Inazaki et al, 2004;Manson, Niederhoff, Hruska, & Austin, 2011a,2011b.…”
Section: Inhibition Of Renal Fibrosismentioning
confidence: 97%
“…First, BMP-7 expression is decreased in pericytes as they differentiate into renal myofibroblasts, suggesting the possibility that BMP-7 inhibits pericyte differentiation and/or myofibroblast function in an autocrine manner (Lin et al, 2008). Furthermore, treatment with BMP-7 following chronic renal injury suppresses the TGF-β-dependent expression of α-SMA (a cytoskeletal protein that is necessary for myofibroblast contractility and upregulated during myofibroblast differentiation) and Collagen Iα1 (the primary matrix protein secreted by myofibroblasts in fibrosis) (Manson et al, 2011a(Manson et al, ,2011b. Finally, treatment with BMP-7 prevents the accumulation of myofibroblasts and renal fibrosis in models of CKD (see Table 1).…”
Section: Inhibition Of Renal Fibrosismentioning
confidence: 99%